Recirculation of digestive enzymes - G. F. Korot'ko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
The aim of review. To present literature data and to generalize accumulated by the author and his employees experimental and clinical material on the mechanisms of enzyme transport to systemic blood flow, process of recretion of enzymes by digestive glands in the lumen of gut and the functional role of circulating hydrolases.Original positions. Digestive glands exosecrete two pools of hydrolases: postprandially de novo synthesized and recreted from blood circulation, to which they are transported by three mechanisms – endosecretion of glandular cells, resorption of hydrolases from ductal system of the glands and the small bowel. Enzymes, being switched off from circulation by recretion, are involved in gastro-intestinal digestion and carry out a signal role in modulation of secretory, motor and absorptive functions of the gut. Circulation and recretion of enzymes, their reutilization in alimentary process fit into principle of energetic and plastic economization in alimentary functions.Conclusion. The principle of enterohepatic circulation of bile acids in general view is repeated at interorgan recirculation of hydrolases of the digestive glands providing process of digestion, and by enzyme signaling – integration and adaptation of functions of the gut organs by modulating effects.